THE STUDY OF THE DYNAMIC PROPERTIES OF THE ARTICULATED FLAT-CAR ON MATHEMATICAL MODELS - Rudakova, E. O.; Orlova, A. M. (Science and Transport Progress, 2008)
The paper is devoted to the study of dynamic qualities of combined tractive connection of two18 mplatform wagons with installing the removable equipment for transportation of three 40-foot containers developed by the JSC «NVTs «Vagony» according to order of the JSC «TransContainer». The calculations performed allowed determining the schemes of loading ensuring the normative indices of running qualities and traffic safety.